Design framework for multifunctional additive manufacturing: coupled optimization strategy for structures with embedded functional systems - Panesar, Ajit; Ashcroft, Ian; Brackett, David; Wildman, Ricky D.; Hague, Richard (Elsevier, 2017)
The driver for this research is the development of multi-material additive manufacturing processes that provide the potential for multi-functional parts to be manufactured in a single operation. In order to exploit the potential benefits of this emergent technology, new design, analysis and optimization methods are needed. This paper presents a method that enables in the optimization of a multifunctional part by coupling both the system and structural design aspects. This is achieved by incorporating the effects of a system, comprised of a number of connected functional components, on the structural response of a part within a structural topology optimization procedure. The potential of the proposed method is demonstrated by performing a coupled optimization on a cantilever plate with integrated components and circuitry. The results demonstrate that the method is capable of designing an optimized multifunctional part in which both the structural and system requirements are considered.